Enhancing Disaster Resilience by Reducing Stress-Associated Health Impacts - Sandifer, Paul A.; Walker, Ann Hayward (Frontiers in Public Health, 2018)
Disasters are a recurring fact of life, and major incidents can have both immediate and long-lasting negative effects on the health and well-being of people, communities, and economies. A primary goal of many disaster preparedness, response, and recovery plans is to reduce the likelihood and severity of disaster impacts through increased resilience of individuals and communities. Unfortunately, most plans do not address directly major drivers of long-term disaster impacts on humans – that is, acute, chronic, and cumulative stress -- and therefore do less to enhance resilience than they could. Stress has been shown to lead to or exacerbate ailments ranging from mental illness, domestic violence, substance abuse, post-traumatic stress disorders, and suicide to cardiovascular disease, respiratory problems, and other infirmities. Individuals, groups, communities, organizations, and social ties are all vulnerable to stress. We summarize selected literature about disasters, resilience, and disaster-associated stress effects and recommend eight actions to improve resiliency through inclusion of stress alleviation in disaster planning: (1) Improve existing disaster behavioral and physical health programs to better address, leverage, and coordinate resources for stress reduction, relief, and treatment in disaster planning and response. (2) Emphasize pre- and post-disaster collection of relevant biomarker and other health-related data to provide a baseline of health status against which disaster impacts could be assessed, and continued monitoring of these indicators to evaluate recovery. (3) Enhance capacity of science and public health early-responders. (4) Use natural infrastructure to minimize disaster damage. (5) Expand the geography of disaster response and relief to better incorporate the displacement of affected people. (6) Utilize nature-based treatment to alleviate pre- and post-disaster stress effects on health. (7) Review disaster laws, policies, and regulations to identify opportunities to strengthen public health preparedness and responses including for stress-related impacts, better engage affected communities, and enhance provision of health services. (8) With community participation, develop and institute equitable processes pre-disaster for dealing with damage assessments, litigation, payments, and housing.